Surveillant Intimacies - Hogan, Mél (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2018)
We often think of surveillance as ubiquitous, secretive, top-down, corporate, and governmental—and in many ways, it is. Through three vignettes, this essay prods at the ways in which our everyday tools, technologies, and gestures extend surveillance’s reach into our intimate lives and relationships. Each vignette is a story constructed from facts gleaned in news stories, social media, or personal conversations. As such, these vignettes are neither empirical nor entirely speculative. In an effort to consider surveillance as an ongoing and daily activity, they invite readers into more intimate contexts than those that are usually the object of rigorous scholarly analysis. In their intimacy, these stories serve to remind us of the ways in which communication devices are always, in some capacity, tracking and trailing our desires.Vignette 1 tells the story of the NSA agent who uses the agency’s powerful database to spy on an ex-lover. Vignette 2 explores the kinds of information users can get (about themselves) from Big Tech companies, from social media and dating apps. Vignette 3 looks at Internet cookies and their capacity to make unlikely—and unwanted—introductions. Technology, apps, and our always-on devices complicate the boundaries of intimacy and often work to redefine the trajectories of our desire in the process. The breaches of trust detailed in these stories expose the ways in which Big Tech’s desire to predict and to measure human emotion and behaviour exists in tension with our memories, our secrets, and our wild imaginations.